2012
DOI: 10.1007/s00192-012-1765-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of occult stress urinary incontinence (OSUI) following vaginal prolapse surgery: long-term follow-up

Abstract: Despite the preoperative evidence of OSUI, the manifestation of SUI rarely occurs, with 28.1 % of patients experiencing SUI over long-term follow-up after vaginal prolapse surgery. Anti-incontinence surgery was necessary in only three cases (5.3 %). These results indicate that with the one-step approach, 54 of 57 patients (94.7 %) would have received prophylactic anti-incontinence surgery unnecessarily. In conclusion, we recommend the two-step approach in the management of vaginal prolapse surgery in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 22 publications
(25 reference statements)
2
19
2
Order By: Relevance
“…As noted by Ennemoser et al, 28.1% of patients with OSUI developed POSUI after a period of 5.7 years. 30 But in our study none of the patients developed POSUI. This difference may be due to short term follow up.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…As noted by Ennemoser et al, 28.1% of patients with OSUI developed POSUI after a period of 5.7 years. 30 But in our study none of the patients developed POSUI. This difference may be due to short term follow up.…”
Section: Discussioncontrasting
confidence: 60%
“…Hence they recommended the two-step approach in the management of vaginal prolapse surgery in patients with OSUI. 30 In a study by Klutke and Ramos et al, the prophylactic Burch colposuspension increased the incidence of UI. Hence they had suggested the requirement of preoperative testing to identify the women who require an anti-incontinence procedure.…”
Section: Discussionmentioning
confidence: 97%
“…6,7,31,35,49,50 Based on the five studies including asymptomatic women (19/85) and those included in our meta-analysis (27/124), we estimated roughly that, overall, about 22% (46/209) of the women with de novo SUI would request a subsequent anti-incontinence procedure. 6,7,10,11,24,27,31,49,50 This meta-analysis showed that the incidence of adverse events related to tape placement was higher in the group undergoing combination surgery relative to vaginal prolapse surgery only. There are two possible reasons for this increased risk: (1) the presence of POP is an isolated risk factor for the development of a complication; and/or (2) with the addition of a surgical procedure, the risks also increase.…”
Section: Interpretation In the Light Of Other Evidencementioning
confidence: 99%
“…[3][4][5] The risk is assumed to be highest (up to 80%) in the 20-30% of continent women with occult SUI, and is believed to be associated with kinking or compression of the urethra by the prolapse. [3][4][5][6][7] The combination of prolapse surgery with an anti-incontinence procedure to treat or prevent SUI is frequently considered in three patient groups: (1) women with coexisting SUI; (2) women asymptomatic for SUI; and (3) women asymptomatic for SUI with occult SUI.…”
Section: Introductionmentioning
confidence: 99%
“…In the follow-up period (mean 31 months) SUI was reported in 71.4 % in the TVT group and 77.3% in the TOT group of patients. Average satisfaction level was 9 (range 1-10) In a study by Ennemoser and colleagues at the Department of Obstetrics and Gynecology, University of Munich, Germany in 2012 on patients with pelvic organ prolapse surgery, the rate of stress incontinence was 28.1% in the follow-up period which only 5.3% of the patients required further surgery for incontinence (22). In our study complained of urinary incontinence in patients with prophylactic surgery in 3 patients (10%) were found in patients without prophylactic surgery of urinary incontinence after surgery, 5 patients (16.66%) were in patients with prophylactic surgery than patients without prophylactic surgery, but this difference was not significant.…”
Section: Discussionmentioning
confidence: 99%